THE SYSTEM OF REVENUE ON FISHERMEN USING BEACH SEINE IN PADANG COASTAL OF WEST SUMATERA PROVINCE - Hades Mandela; Zulkarnaini '; Hendrik ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study aims to determine the system of revenue in Padang coastal using beach seine. The survey was conducted in Padang West Sumatra province on 20-27 November 2015. This study used a survey method with the respondents are 2 fisherman owner and 24 fishermen workers.Based on the results of the research showed that businesses in Padang coastal using beach seine can be classified into two types of business that is the family business and non-family businesses, both these companies influence is done on the system of revenue. The system of revenue on family business more emphasis on kinship so hard to the standard rules relating to the sharing this system while the system of revenue on non-family business in force define 33 % for fishermen owner and 67 % for fishermen workers. The percentage of the income of fishermen owners greater in comparison to the percentage of fishermen workers both family and non-family business.Keywords: System, revenue, income, fishermen, beach seine.